Simplifying
3[-1x + (2x + 1)] = x + -1
Reorder the terms:
- 3[-1x + (1 + 2x)] = x + -1
Remove parentheses around (1 + 2x)
Reorder the terms:
Combine like terms: -1x + 2x = 1x
- [1 * 3 + 1x * 3] = x + -1
Reorder the terms:
Solving
Solving for the variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-1x' to each side of the equation.
- 3 + 3x + -1x = -1 + x + -1x
Combine like terms: 3x + -1x = 2x
Combine like terms: x + -1x = 0
- 3 + 2x = -1 + 0
- 3 + 2x = -1
Add '-3' to each side of the equation.
3 + -3 + 2x = -1 + -3
Combine like terms: 3 + -3 = 0
- 0 + 2x = -1 + -3
- 2x = -1 + -3
Combine like terms: -1 + -3 = -4
Divide each side by '2'.
Simplifying